2020
DOI: 10.1016/j.pedneo.2020.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of congenital hypothyroidism in a cohort of preterm born children

Abstract: Background: Congenital hypothyroidism (CH) is reported to be more common in preterm infants than in term infants, especially in sick preterm infants. Though a frequent possibility of transitory thyroidal alterations in this category of neonates, the evolution of CH to transient or permanent forms is unpredictable. Methods: We retrospectively analyzed medical records of 28 preterm infants (<37 weeks gestation) who had exhibited a positive screening for CH at birth during the period 2000 e2015 followed in our Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
(27 reference statements)
0
3
0
1
Order By: Relevance
“…Umbilical cord blood TSH measurement has shown several advantages, including non-invasive, easy sampling, and recheck enabling even before the mother leaves the hospital. However, some studies have demonstrated that the values for CBTSH can be affected by a variety of maternal neonatal factors, while these reports were accompanied by paradoxical and different results (1,3,13,19). In this study, the data of effect of maternal and neonatal factors on cord blood Free T4 and TSH were demonstrated, which were studied in neonates born at Amir-Al-Momenin, Semnan, Iran.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Umbilical cord blood TSH measurement has shown several advantages, including non-invasive, easy sampling, and recheck enabling even before the mother leaves the hospital. However, some studies have demonstrated that the values for CBTSH can be affected by a variety of maternal neonatal factors, while these reports were accompanied by paradoxical and different results (1,3,13,19). In this study, the data of effect of maternal and neonatal factors on cord blood Free T4 and TSH were demonstrated, which were studied in neonates born at Amir-Al-Momenin, Semnan, Iran.…”
Section: Discussionmentioning
confidence: 74%
“…Congenital hypothyroidism (CH) is the most frequent endocrine disorder in newborns. With increasing the incidence rate of congenital hypothyroidism during the past two decades, early diagnosis can dramatically decrease the burden of mentally retarded children in society (19). Umbilical cord blood TSH measurement has shown several advantages, including non-invasive, easy sampling, and recheck enabling even before the mother leaves the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…These previous studies examined the frequency of hypothyroidism within their respective cohorts without differentiating between severe and mild permanent hypothyroidism. [23,25,26,28,[32][33][34]. Detailed comparability between the studies was restricted because of the diversity of selected cohorts (e.g., (very) low birth weight, or preterms below 32, 33, or 37 weeks of gestation), differing screening algorithms (timing and cut-off values) and varying case definitions.…”
Section: Discussionmentioning
confidence: 99%
“…Nesse sentido, estudos demonstram que fatores como idade gestacional, peso ao nascer, níveis de b-TSH no primeiro NBS, s-TSH basal, dose de L-T4 12 m e idade no início do tratamento podem ser considerados elementos preditivos úteis para a evolução do hipotireodismo congênito (Scavone et al, 2020).…”
Section: Hipotireoidismo E Prematuridadeunclassified